hASH1在肺神经内分泌肿瘤中的表达及其临床意义 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: Human achaete-scute homolog 1 (hASH1) gene plays a critical role in development of the central nervous system, automatic nervous system, adrenal medullary chromaffin cells, thyroid C cells and pulmonary neuroendocrine cells. The aim of this study is to determine hASH1 gene expression in the normal lung tissue and various types of lung tumors, to analyze whether its expression correlated with pulmonary neuroendocrine markers, and to explore the possibility of hASH1 as clinical pathological markers in the neuroendocrine tumors compared with previous neuroendocrine tumor markers. METHODS: hASH1, Chromogranin A, Synaptophysin and CD56 expression were examined in lung tumor specimens (lung inflammatory pseudotumor, squamous cell carcinoma, adenocarcinomas, large cell carcinoma, typical carcinoids, atypical carcinoids, large cell neuroendocrine carcinomas and small cell lung carcinoma and corresponding normal lung specimens) using immunohistochemistry (S-P method). Western blot and reverse transcription polymerase chain reaction (RT-PCR) assay were applied to detect the expressions of hASH1 protein and mRNA in lung cancer tissues. RESULTS: hASH1 expression was positive in 2/16 (12.5%) typical carcinoids, 15/20 (75%) atypical carcinoids, 6/10 (60%) large cell neuroendocrine carcinomas and 31/40 (77.5%) small cell lung carcinoma, respectively, but not in any normal lung tissue (0/10), lung inflammatory pseudotumor (0/49), squamous cell carcinoma (0/30), adenocarcinomas (0/30) or large cell carcinoma (0/20). There was a significant difference in hASH1 expression between typical carcinoids and atypical carcinoids (P < 0.01), but not in large cell neuroendocrine carcinomas and small cell lung carcinoma (P > 0.05). hASH1 expression highly closely correlated with Chromogranin A, Synaptophysin and CD56 expression (P < 0.05). CONCLUSION: hASH1 is a new kind of highly specific markers of pulmonary neuroendocrine tumours, and may be applied to clinical pathology diagnosis of the pulmonary neuroendocrine tumors.